Comprehensive Structural, Chemical, and Optical Characterization of Cu2ZnSnS4 Films on Kapton Using the Automated Successive Ionic Layer Adsorption and Reaction Method - Perla J. Vázquez-González; Martha L. Paniagua-Chávez; Lizette A. Zebadua-Chavarria; Rafael Mota-Grajales; C. A. Meza-Avendaño; Enrique Campos-González; A. Escobosa-Echavarría; Yaoqiao Hu; Aldo E. Pérez-Ramos; Manuel-Matuz; Carlos A. Hernández-Gutiérrez (Nanomaterials, 2025)
This study provides a comprehensive structural, chemical, and optical characterization of CZTS thin films deposited on flexible Kapton substrates via the Successive Ionic Layer Adsorption and Reaction (SILAR) method. The investigation explored the effects of varying deposition cycles (40, 60, 70, and 80) and annealing treatments on the films. An X-ray diffraction (XRD) analysis demonstrated enhanced crystallinity and phase purity, particularly in films deposited with 70 cycles. These films exhibited a notable reduction in secondary phases in the as-deposited state, with further improvements observed after annealing at 400 °C and 450 °C in a sulfur atmosphere. A pole figure analysis indicates a decrease in texture disorder with annealing, suggesting improved crystalline orientation at higher temperatures. Field emission scanning electron microscopy (FE-SEM) showed enhancements in surface morphology, with increased grain size and uniformity post-annealing. Chemical uniformity was confirmed through Secondary Ion Mass Spectrometry (SIMS), Energy-Dispersive Spectroscopy (EDS), and X-ray Photoelectron Spectroscopy (XPS). XPS revealed the presence of CZTS phases alongside oxidized phases. Annealing effectively reduced secondary phases, such as ZnO, SnO2, CuO, and SO2, enhancing the CZTS phase. An optical analysis demonstrated that annealing at 200 °C in an air atmosphere reduced the band gap from 1.53 eV to 1.38 eV. In contrast, annealing at 400 °C and 450 °C in a sulfur atmosphere increased the band gap to 1.59 eV and 1.63 eV, respectively. The films exhibited p-type conductivity, as inferred from a valence band structure analysis. Density Functional Theory (DFT) calculations provided insights into the observed band gap variations, further substantiating the findings.